3D printing of soft thermoplastic elastomers: Effect of the deposit angle on mechanical and thermo-mechanical properties. (February 2022) - Tayeb, Adel; Le Cam, Jean-Benoit; Loez, Bruno
Abstract: This work presents the first experimental characterization of the mechanical and thermomechanical properties of a soft 3D printed thermoplastic styrenic elastomer. The tested specimens were obtained by Fused Deposition Modeling with a modified commercial 3D printer. Three different deposit strategies (deposit angle of 0 °, 45 ° and ± 45 ° ) have been tested. Scanning electronic Microscopy was used for analyzing the microstructure of the printed specimens. The specimens were tested under two different uniaxial tensile loadings. The first one consists in applying several sets of load–unload cycles at three increasing strain levels. The second one corresponds to one load–unload cycle at different loading rates. For both tests, the temperature variations were characterized by means of infrared thermography. Results showed that the printing strategy does not have a significant effect on the mechanical response, including the softening, the hysteresis loop and the permanent set, but has an effect on its thermal response. Differences found in terms of self-heating due to intrinsic dissipation clearly show that the deposit angle influences the viscosity of the specimens. Highlights: Specimens of soft TPE-S were printed by Fused Deposition Modeling. Three different deposit angles were considered. Thermo-mechanical properties were characterized. The printing strategy has not a significant effect on the mechanical response. It has a more significant effect on the thermal response, especially the self-heating.